Strategic Management-Based Entrepreneurship Education to Improve Students' Entrepreneurial Spirit - Moh. Rofik; Mohammad Firmansyah; Febi Febrianto; Rausyan Fikri; Aminullah; Muhammad Durrin Ni’am; Mohammad Abdul Aziz Alwahedi (Khatulistiwa Insight: Islamic Education and Learning, 2026)
This study examines the principal's strategic management-based entrepreneurship education in enhancing students' entrepreneurial spirit at Madrasah Aliyah Nurul Yaqin. The study used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation with the principal, entrepreneurship teachers, and students as informants. The results showed that the principal implemented strategic management through practice-based entrepreneurship program planning, organizing student activities, and continuous evaluation. The implementation of this strategy encouraged students' active involvement in entrepreneurial activities, from planning to business evaluation. The impact was seen in increasing students' self-confidence, responsibility, independence, discipline, and problem-solving abilities. This study concluded that the principal's strategic management played an effective role in developing students' entrepreneurial spirit at Madrasah Aliyah Nurul Yaqin.